FOREIGNIZATION AND DOMESTICATION IN TRANSLATING CULTURE-SPECIFIC ITEMS IN THE ENGLISH TRANSLATION OF AHMAD TOHARI’S LINTANG KEMUKUS - Leni Tiwiyanti (Universitas Nasional, 2016)
ABSTRACT A good translation has become a bridge among different cultures from different countries. The termsforeignization and domestication have been proposed to deal with culture-specific items found in the source text. Both terms have become the focus of arguement in the recent years. The purpose of this research is toidentify translation procedures in translating culture specific items that are termed as foreignizing and domesticating and to identify how foreignization and domestication are applied in translating culture specificitems. The method used is qualitative descriptive method. The data analysis shows that in translating thesource text, translator prefers to apply domestication. There are 74.64% data which are translated usingdomestication and only 23.36% data are translated using foreignization. Domestication is prefered as it willallow target text readers to understand the text easily. Moreover, the minority position of the source textcultureof does not allow foreignization to be applied in a greater extent. Foreignization is only applied totranslate central culture-specific items in order to bring the local nuanse of the source text culture.Keywords: translation, forignization, domestication, culture-specific items